Frequency of Myeloproliferative Leukaemia Virus (MPL) W515L Mutation among Sudanese Patients with Polycythemia Vera - Suliman, Muzna Mohammed Ali; Ibrahim, Ibrahim khider; Gaufri, Nasr Eldeen Ali Mohammed (Gezira Journal of Health Sciences, 2020)
Background: Myeloproliferative leukemia virus (MPL) plays an important role in the development of megakaryocytes and platelets as well as the self-renewal of haematopoietic stem cells. Recently, numerous MPL mutations have been identified in MPN and reported by researchers. These mutations alter the normal regulatory mechanisms and lead to autonomous activation or signaling deficiencies. The present study aimed to detect the frequency of MPL (W515L)mutation gene among Sudanese patients with polycythemia vera (PV).It may lead to new diagnostic criteria or therapy design. Materials and methods: This was a descriptive cross sectional study in which a total of 37 patients with polycythemia vera were enrolled in this study, DNA was extracted from patients’ blood samples by using salting out method, and analyzed for the detection of MPL(W515L) mutation by using allele specific polymerase chain reaction  (ASPCR).Laboratory results and patient’s data were analyzed using statistical packing for social sciences program(SPSS). Results :A total of 37 Sudanese patients attended military hospitals that have been diagnosed with polycythemia vera were enrolled in this study. 36(97.3%) of them were males, one (2.7%) females; age ranged between 23-74 years The present study showed that 10(27.0%) patients out of 37 were positive for MPL (W515L) mutation, and all of them were males. Conclusion: This study concluded that the frequency of MPL W515L mutation in Sudanese patients with polycythemia vera is 27%.